Microsatellite instability evaluation of patients with solid tumour: routine practice insight from a large series of Italian referral centre. Issue 2 (11th May 2022) - Russo, Gianluca; Pepe, Francesco; Pisapia, Pasquale; Palumbo, Lucia; Nacchio, Mariantonia; Vigliar, Elena; Pallante, Pierlorenzo; Parente, Paola; Fassan, Matteo; Graziano, Paolo; Bellevicine, Claudio; Troncone, Giancarlo; et al.
Abstract : DNA mismatch repair complex is involved in the maintenance of DNA stability. In the recent years, a plethora of technical approaches for microsatellite instability (MSI) analysis emerged. Here, we review the results of our MSI status evaluation by adopting a customised workflow on microfluidic system obtained in 4 years of diagnostic routine practice. Data from MSI status were retrieved from our institutional archive covering the period from January 2017 to December 2021. Microfluidic analysis was carried out on microfluidic platform. Results were inspected with a proprietary software. Overall, microsatellite stability (MSS) and MSI-high (MSI-H) profile was detected in n=423/458 (92.36%) and n=35/458 (7.64%) patients with metastatic CRC (mCRC), respectively. In addition, n=78/86 (90.70%) and n=8/86 (9.30%) patients without CRC showed an MSS and MSI-H profile. This review highlights the suitability of microfluidic approach in patients with cancer for MSI testing.